A critical view of the anthropology of religion. Issue 2 (1st April 2021) - Fitzgerald, Timothy
Abstract : Anthropologists who write textbooks or teach undergraduate courses on the topic of 'religion' ought to be more aware of the tradition of critique by religious studies academics of their shared central category. There is a large and growing literature on the modern invention of religion and religions since the colonial era, and the radical shifts in meaning that have occurred in English and other europhone vernaculars since the 17th century. This literature is widely ignored by anthropologists who claim expertise on 'religion'. 'Religion' is a complex, contested product of colonial and class power relations and has been used to control and classify peoples everywhere. The author suggests that the category religion emerged as a placeholder during the colonial era for any institution or practice that impeded (male) private property interests. The idea of 'religion' is by no means as innocent and neutral as it appears.